The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/0957926509360743
|View full text |Cite
|
Sign up to set email alerts
|

‘Oh you don’t want asylum seekers, oh you’re just racist’: A discursive analysis of discussions about whether it’s racist to oppose asylum seeking

Abstract: In this article, we explore how speakers discuss whether or not it is racist to oppose asylum seekers. A discourse analysis is conducted on the parts of a corpus of data collected from focus groups with undergraduate students talking about asylum seeking in which they were asked if it is racist to oppose asylum. It is shown that speakers use the word ‘just’ as part of a contrast structure which is used to present a topic as self-evidently unreasonable. While some participants orient to the taboo against prejud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 37 publications
(64 reference statements)
1
104
0
2
Order By: Relevance
“…This research builds on previous research by Goodman and Burke (2010;2011), who found that speakers constructed accusations of racism towards opponents of asylum as being unreasonable, and attributed their opposition to practical issues such as the economy, which demonstrates Discursive Deracialisation. The aim of this research is therefore to address how accusations of racism are made and rejected in an online setting where the language is less guarded and more extreme.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…This research builds on previous research by Goodman and Burke (2010;2011), who found that speakers constructed accusations of racism towards opponents of asylum as being unreasonable, and attributed their opposition to practical issues such as the economy, which demonstrates Discursive Deracialisation. The aim of this research is therefore to address how accusations of racism are made and rejected in an online setting where the language is less guarded and more extreme.…”
Section: Rationalementioning
confidence: 99%
“…People who oppose asylum seeking often justify their opposition in terms of economic or cultural factors (Lynn and Lea, 2003;Every and Augoustinos, 2007;Capdevila and Callaghan, 2008;Goodman and Burke, 2010;2011) which is a way of disclaiming (Billig et al, 1988) prejudice. Speakers ensure that opposition to asylum is attributed to reasons other than race, which makes the speaker appear to be reasonable.…”
Section: Discursive Psychology and Prejudicementioning
confidence: 99%
See 1 more Smart Citation
“…Research based on focus group data has thus been able to add a more strongly interactional focus to the examination of themes similar to those discussed above, including new racisms and the denial of racism (see, e.g., Augoustinos, Tuffin, & Every, 2005;Goodman & Burke, 2010). Particularly noteworthy in this regard are Condor's (2006) analysis of how participants interactionally collaborate in the production of subtly racist talk, and the extension of previous analyses of denials of racism to consider not just how denials can be produced by a speaker on his/her own behalf, but also how other speakers may deny racism on behalf of others, and may collaboratively suppress potentially racist utterances (Condor, Figgou, Abell, Gibson, & Stevenson, 2006).…”
Section: Focus Groups and Group Discussionmentioning
confidence: 99%
“…First, it highlights the notion of race, which is a potentially problematic area for the BNP to be publically discussing. Second, it also brings about the possibility of Griffin having to deal with all the problems associated with someone who makes accusations of racism (Goodman, 2010;Goodman and Burke, 2010) in addition to those associated with being accused of being a racist (e.g. Edwards 2003).…”
Section: Discussionmentioning
confidence: 99%